Assessing Schema Modes Using Self- and Observer-Rated Instruments: Associations With Aggression. Issue 17 (September 2021) - Lewis, Deborah; Dunne, Ashley L.; Meyer, Denny; Daffern, Michael
This study examined the associations between schema modes and aggression in 59 male forensic psychiatric inpatients. Two instruments were used to assess schema modes: One measured modes through self-report, the Schema Mode Inventory (SMI), and one measured modes via observer (nurse) judgments, the Mode Observation Scale (MOS). Aggression was measured in two ways: Self-reported aggression during participants' lifetimes was assessed using the Life History of Aggression-Self-Report-Aggression Scale (LHA-S-A), and incidents of aggression during hospitalization in the month following schema mode assessment, were identified through review of medical records. Self-reported (SMI) and observer-reported (MOS) measures of schema modes were poorly related and produced disparate associations with aggression. As hypothesized, the observer-reported MOS Angry-Child and MOS Impulsive-Undisciplined-Child modes were significantly associated with aggression during the follow-up. A number of other schema modes (MOS-Healthy-Adult, SMI-Angry-Child, MOS-Complaining-Protector, SMI-Undisciplined-Child, and MOS-Angry-Protector) were unexpectedly associated with aggression.